2014
DOI: 10.1177/0300060514549217
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of admission levels of cardiac indicators in patients with acute ischaemic stroke: Prospective observational study

Abstract: Objective: The performance of cardiac indicators as determinants of stroke outcomes remains debatable, therefore the present study focused on the short-term prognostic value of cardiac indicators in patients who had experienced acute ischaemic stroke. Methods: Consecutive patients with acute ischaemic stroke were enrolled in a prospective stroke registry. Data on demographics, clinical characteristics and cardiac indicator levels (including troponin I, creatine kinase-MB, myoglobin and brain natriuretic peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Stroke in patients with heart failure is associated with more severe neurological deficits and very high rates of cardiovascular morbidity and mortality (Hays 2006;Vemmos 2012). In addition, the association between myoglobin, aortic stiffness, CK-MB, ejection fraction (EF) and adverse outcomes in stroke patients has been widely reported (Liu et al 2014;Rojek 2016). The clinical manifestations of cardiac damage after stroke and its impact on the patient's prognosis have been a hot topic of discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke in patients with heart failure is associated with more severe neurological deficits and very high rates of cardiovascular morbidity and mortality (Hays 2006;Vemmos 2012). In addition, the association between myoglobin, aortic stiffness, CK-MB, ejection fraction (EF) and adverse outcomes in stroke patients has been widely reported (Liu et al 2014;Rojek 2016). The clinical manifestations of cardiac damage after stroke and its impact on the patient's prognosis have been a hot topic of discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Another similar study was performed in China by Liu et al 18 regarding the short-term prognostic value of cardiac indicators in patients who had experienced acute ischemic stroke. They studied various cardiac biomarkers and concluded that myoglobin may be an independent predictor of short-term outcomes in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 73%
“…14 stroke severity was assessed via National Institutes of Health Stroke Scale (NIHSS). The following classes were made based on NIHSS scores Mild<5, Mild to Moderately severe, severe [15][16][17][18][19][20][21][22][23][24] and very severe >25.15 Subjects and their caregivers were provided with a detailed description of the study and were inducted into the study after written informed consent. Subjects with confounding variables like the presence of cardiac illness or skeletal conditions were identified by detailed history taking and excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiometabolic disturbance has been associated with early mortality and a poor prognosis in patients with stroke ( 28 , 29 ). A study identified several cardiac complications after 2 days of intracerebral hemorrhage and 3 months of ischemic stroke ( 6 , 30 ).…”
Section: Discussionmentioning
confidence: 99%